PENGIMPUTASIAN KEBENARAN KRISTUS: AJARAN ALKITAB ATAU PENALARAN DOGMATIS - Dick Mak (Phronesis: Jurnal Teologi dan Misi, 2020)
Discussions about the meaning of imputation play an important role in the spirtuality of believers. This research attempts to show the meaning of justification in the Christians life of believers as imputation of Christ's truth. The Lord Jesus did not sin at all in his life. So, the truth refers to right behavior or life, not to status. This research examines how the development of thought in the modern age has made significant contributions to Christianity. This view stems from a new approach to Paul's theology, called The New Perspective on Paul. This research shows how faith is a means of imputing that truth. In Romans 4 the truths which are accounted for to the believer are not explained further. But in Philippians 3: 9 and 2 Corinthians 5:21 we find the terms "righteousness of God" and "righteousness which comes from God". These two passages lend support to the dogmatic term iustitia aliena, 'foreign' truth, which does not originate with the believer himself.